Ultrasound Microbubble–Facilitated Inner Ear Delivery of Gold Nanoparticles Involves Transient Disruption of the Tight Junction Barrier in the Round Window Membrane - Lin, Yi-Chun; Shih, Cheng-Ping; Chen, Hsin-Chien; Chou, Ying-Liang; Sytwu, Huey-Kang; Fang, Mei-Cho; Lin, Yuan-Yung; Kuo, Chao-Yin; Su, Hsiao-Han; Hung, Chia-Lien; Chen, Hang-Kang; Wang, Chih-Hung (Frontiers in Pharmacology, 2021)
The application of ultrasound microbubbles (USMBs) enhances the permeability of the round window membrane (RWM) and improves drug delivery to the inner ear. In this study, we investigated the efficiency of USMB-aided delivery of chitosan-coated gold nanoparticles (CS-AuNPs) and the mechanism of USMB-mediated enhancement of RMW permeability. We exposed mouse inner ears to USMBs at an intensity of 2 W/cm2 and then filled the tympanic bulla with CS-AuNPs or fluorescein isothiocyanate-decorated CS-AuNPs (FITC-CS-AuNPs). The membrane uptake of FITC-CS-AuNPs and their depth of permeation into the three-layer structure of the RWM, with or without prior USMB treatment, were visualized by z-stack confocal laser scanning microscopy. Ultrastructural changes in the RWM due to USMB-mediated cavitation appeared as sunburn-like peeling and various degrees of depression in the RWM surface, with pore-like openings forming in the outer epithelium. This disruption of the outer epithelium was paralleled by a transient reduction in tight junction (TJ)-associated protein levels in the RWM and an enhanced delivery of FITC-CS-AuNPs into the RWM. Without prior USMB exposure, the treatment with CS-AuNPs also caused a noticeable reduction in TJ proteins of the RWM. Our findings indicated that the combined treatment with USMBs and CS-AuNPs represents a promising and efficient drug and gene delivery vehicle for a trans-RWM approach for inner ear therapy. The outer epithelial layer of the RWM plays a decisive role in controlling the transmembrane transport of substances such as CS-AuNPs following the administration of USMBs. Most importantly, the enhanced permeation of AuNPs involved the transient disruption of the TJ-created paracellular barrier in the outer epithelium of the RWM.